Prevalence of Internet Addiction Disorder and Its Correlates Among Clinically Stable Adolescents With Psychiatric Disorders in China During the COVID-19 Outbreak - Li, Zong-Lei; Liu, Rui; He, Fan; Li, Shu-Ying; Zhao, Yan-Jie; Zhang, Wu-Yang; Zhang, Yao; Cheung, Teris; Jackson, Todd; Tang, Yi-Lang; Xiang, Yu-Tao (Frontiers in Psychiatry, 2021)
Background: Since the Coronavirus disease 2019 (COVID-19) pandemic emerged, Internet usage has increased among adolescents. Due to this trend, the prevalence of Internet addiction disorder (IAD) may have increased within this group. This study examined the prevalence of Internet addiction disorder (IAD) and its correlates among clinically stable adolescents with psychiatric disorders in China during the COVID-19 outbreak. Method: A multi-center, cross-sectional study was carried out between April 29 and June 9, 2020 in three major tertiary mental health centers in China. IAD and depressive symptoms were assessed using the Internet Addiction Test (IAT) and the 9-item Patient Health Questionnaire (PHQ-9), respectively. Results: A total of 1,454 adolescent psychiatric patients were included in final analyses. The prevalence of IAD was 31.2% (95% CI: 33.6%-28.8%) during the COVID-19 pandemic. A multiple logistic regression analysis revealed that poor relationships with parents (P<0.001, OR=2.34, 95%CI: 1.49-3.68) and elevated total PHQ-9 scores (P<0.001, OR=1.19, 95%CI: 1.16-1.21) were significantly associated with higher risk for IAD while longer daily physical exercise durations (P=0.04, OR= 0.67, 95%CI: 0.46-0.98) and rural residence (P=0.003, OR=0.62, 95%CI: 0.46-0.85) were significant correlates of lower risk for IAD. Conclusions: IAD was common among adolescent patients with clinically stable psychiatric disorders during the COVID-19 pandemic; regular physical exercise, healthy relationships with parents and fewer symptoms of depression were correlated with reduced risk within this population.